Mga pangulo ng Pilipinas - Garcia, Lydia Gonzales (Mga saligang aklat, 1991)
This biographical source is written in Filipino and concentrates on the Philippine presidents' accomplishments and experiences, from Emilio Aguinaldo to Fidel Ramos. A black and white illustration and a quote attributed to each president starts each feature article. It includes facts as anecdotes. A boxed summary of the article is found at the end of each article.